Investigating accounting factors through audited financial statements in businesses toward a circular economy: Why a sustainable profit through qualified staff and investment in technology? - Enkeleda Lulaj; Blerta Dragusha; Eglantina Hysa (Administrative Sciences, 2023)
This study examines the investigation of accounting factors through audited financial statements in businesses by analyzing the qualified staff and investment in technology for sustainable profit. Therefore, the main goal is to analyze whether qualified staff and investment in technology affect the sustainability of profit in businesses through the investigation of accounting factors in the audited financial statements toward a circular economy, more specifically in these financial items: total assets (TASS), and intangible assets (IASS), total liabilities (TLIA), total income (TREV), and net financial income (NFI), based on questions about which financial items businesses should take care of, as well as businesses that do not invest in technologies and skilled staff: does this hinder profit sustainability? Therefore, for this study, data are collected from the financial statements (balance sheet and income statement) of (N = 800) businesses according to their activity (manufacturing businesses = 256, service businesses = 192, and distribution businesses = 353) during the period (2020-2022). The results show that each of the variables and factors had a significant impact on sustainable profit through the circular economy in (N = 800) businesses. However, to have a sustainable profit in business, it is strongly recommended to pay attention to these findings: businesses should (a) be careful with total liabilities, (b) increase the performance of total assets, (c) increase the performance of net financial income, (d) increase the performance of total business income, and (e) increase and develop the skills of workers, as well as improve technology (equipment, machinery, etc.). With implications and limitations, it was difficult to access some of the financial statements; there are only a limited number of variables, so the same models can be analyzed for other businesses, variables, and countries.
Keywords: 350; accounting; auditing; businesses; circular economy; financial statements; sustainable profit